URBANIZATION AND BIODIVERSITY: THE NATURALIZATION OF URBAN DEVELOPMENT. - Solijonova Raykhona (TADQIQOTLAR, 2025)
Abstract: Today a large part of the world’s population lives in cities. The process of urbanization continues at a rapid pace, and this process affects all aspects of human life. Cities are expanding, new infrastructures are being built, economic and cultural life is developing. However, not only does urbanization remain associated with human activities, it also has a significant impact on the natural environment and biodiversity. The naturalization of urban development is understood as the harmonization of the urbanization process with nature, actions aimed at preserving and developing biodiversity. This article discusses the impact of urbanization on biodiversity, the integration of cities with the natural environment, the development of urban ecosystems and the challenges and prospects in this process.